2018
DOI: 10.1038/s41586-018-0563-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant functional trait change across a warming tundra biome

Abstract: Plant functional trait change across a warming tundra biomeThe tundra is warming more rapidly than any other biome on Earth, and the potential ramifications are far-reaching because of global feedback effects between vegetation and climate. A better understanding of how environmental factors shape plant structure and function is crucial for predicting the consequences of environmental change for ecosystem functioning. Here we explore the biome-wide relationships between temperature, moisture and seven key plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
513
9
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 536 publications
(562 citation statements)
references
References 85 publications
37
513
9
3
Order By: Relevance
“…Hudson et al () found that most species showed increased leaf size and plant height under a warming treatment and that traits related to growth were more affected by warming than leaf nitrogen content. Similarly, Bjorkman et al () found comparable intraspecific responses of plant traits, such as plant height, LA and SLA, to temperature gradients.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Hudson et al () found that most species showed increased leaf size and plant height under a warming treatment and that traits related to growth were more affected by warming than leaf nitrogen content. Similarly, Bjorkman et al () found comparable intraspecific responses of plant traits, such as plant height, LA and SLA, to temperature gradients.…”
Section: Discussionmentioning
confidence: 73%
“…While LA tended to increase across all plant species (+19.6% on average), this shift likely resulted from a modification of resource allocation driven by changes in SLA, such as an expansion of the foliar lamina associated with a decrease in leaf thickness. Hence, higher temperature likely enhances plant metabolism, favouring higher rates of cell expansion and facilitating faster production of softer tissues (Atkin, Botman, & Lambers, ; Körner, ); temperature is thus generally positively related to SLA at the intra‐ and interspecific level (Bjorkman et al, ; Woodward, ). Hudson et al () found that most species showed increased leaf size and plant height under a warming treatment and that traits related to growth were more affected by warming than leaf nitrogen content.…”
Section: Discussionmentioning
confidence: 99%
“…In a manipulative experiment in a salt marsh in Georgia, USA, Dai and Wiegert () have shown that the productivity of S. alterniflora significantly increases after N addition, and that 79% of this increment is explained by leaf area, while just 21% is explained by leaf N. These results suggest that, in salt marshes, size‐related traits are more sensitive to geographic variation in exogenous nutrient inputs than leaf economic traits (e.g., SLA, leaf N and P) (Bjorkman et al. ). These size‐related traits potentially play a significant role in conferring a competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…This ‘traits manifesto’ (Reich, ) has seen a dramatic rise in popularity in recent years, improving our understanding of community assembly (Siefert et al ., ) and ecosystem responses to warming (Soudzilovskaia et al ., ). However, progress is hampered by fundamental unknowns regarding the nature of trait variation and physiological tradeoffs (Siefert et al ., ; Díaz et al ., ; Shipley et al ., ), by issues of prediction across scales (Messier et al ., ), and by uneven data coverage among traits, species, and ecosystems (Iversen et al ., ; Jetz et al ., ; Bjorkman et al ., ,b). For trait‐based ecology to reach its full potential, trait–function relationships must be tested across the world's biomes, including in our planet's most extreme environments.…”
Section: Introductionmentioning
confidence: 99%